Maximizing rehabilitation outcomes in geriatric hip fracture patients: the impact of surgical variables: Optimizing Rehabilitation Success in Geriatric Hip Fracture Surgery - Amata, Oriana; Ridolo, Erminia; Costantino, Valeria; Panella, Lorenzo; Incorvaia, Cristoforo; Caserta, Antonello Valerio; Callegari, Camilla (Acta Biomedica Atenei Parmensis, 2023)
Background and aim:Hip fracture is a major traumatic event with high mortality and disability rate. Its management in the acute setting and in the rehabilitation process is highly debated. This study evaluates the possible determinants of hip fracture rehabilitation outcome, among which surgical intervention type, weight-bearing status and hospitalization lengthMethods:The data of 738 hip fracture patients, who completed rehabilitation process in our centre, were collected and patients’ functional abilities at the time of admission and discharge were analysed.Results:It has been observed that functional recovery depends on several factors: the type of surgery, the post-operative course and related complications, the hospitalisation time, the surgeon’s techniques and expertise and the Orthopaedics centre where the operation is performed.Conclusions:In conclusion, data integration in perspective of an individualised rehabilitation program appears crucial for the functional recovery of the hip fracture patient.